Revisiting the single-eyelid hughes reconstruction – A report of two cases - Spencer Harris; Rona Z. Silkiss (American Journal of Ophthalmology Case Reports, 2022)
Purpose: The reconstruction of near-total upper eyelid defects is challenging and complicated. There are multiple possible techniques, including multi-stage lower eyelid flaps (such as Mustarde's lid-switch flap and the Cutler-Beard techniques) as well as single-stage techniques with free grafts. Here we present two patients requiring near-total upper eyelid repairs that were accomplished by a single-eyelid, single-stage technique using a tarsoconjunctival flap. Observations: Two cases of near-total upper eyelid defects are described, one secondary to resection of a basal cell carcinoma and the other secondary to resection of a Merkel cell carcinoma. Both cases had sufficient residual tarsus to supply a single-eyelid tarsoconjunctival flap. Results were excellent. Conclusions: When there is sufficient tarsus remaining, the illustrated technique provides an excellent repair of near-total upper-eyelid defects. It is a simpler procedure than its alternatives, spares other tissue sites, eliminates free grafts, and does not require multiple stages.